Performance evaluation of lossless RoCEv2 network in HPC cluster - LONG Tingting; FU Zhenxin; LI Ruomiao; GONG Xiangyu; WU Tao; FAN Chun (Tongxin xuebao)
To evaluate the practical performance of lossless RoCEv2 network technology in the HPC field, an HPC cluster was set up using three types of networks: lossless RoCEv2, TCP/IP, and InfiniBand. Mainstream HPC benchmarks and scientific computing applications were used to compare these networks, obtaining basic performance data and actual performance in scientific computing scenarios. The HPL efficiency of a 240-node cluster based on RoCEv2 was also tested. The experimental results show that in supercomputing clusters, lossless RoCEv2 has performance roughly equivalent to InfiniBand and is significantly superior to TCP networks. As the number of cluster nodes increases, the RoCEv2 network demonstrates good linear scalability. Compared to InfiniBand, the lossless RoCEv2 network maintains a cost advantage while offering approximately equivalent performance.